Bianchi type-II string-dust universes - Ram S.; Singh P. (My University, 2025)
We present an exact solution of Einstein's equations for cosmological models of Bianchi type-II filled with string dust as the source for the gravitational field. The solution represents an expanding and anisotropic universe which would give essentially an empty universe for large time. Some kinematical properties of the solution are discussed. © 1992 Kluwer Academic Publishers.